1991
DOI: 10.5014/ajot.45.11.998
|View full text |Cite
|
Sign up to set email alerts
|

The Narrative Nature of Clinical Reasoning

Abstract: Narrative reasoning is a central mode of clinical reasoning in occupational therapy. Therapists reason narratively when they are concerned with disability as an illness experience, that is, with how a physiological condition is affecting a person's life. In this paper, narrative reasoning is contrasted with propositional reasoning, and two kinds of narrative thinking are examined. The first is the use of narrative as a mode of speech that can be contrasted with biomedical discourse, in which disability is fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
197
1
8

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 278 publications
(209 citation statements)
references
References 4 publications
3
197
1
8
Order By: Relevance
“…Evaluative work surrounding expertise and novice practice shows similarities between professions, especially in common decision-making skills (Curran et al 2006;Hoben et al 2007;Mattingly 1991). Expert practice in physiotherapy has been proposed to involve a combination of knowledge, clinical reasoning, movement and virtues (Jensen et al 2000), whilst "master" or expert practice when compared to novice has been shown to be separated by the ability to use time, develop frameworks, communicate, teach, and predict clinical outcomes (Jensen et al 1992).…”
Section: Methods Of Reasoningmentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluative work surrounding expertise and novice practice shows similarities between professions, especially in common decision-making skills (Curran et al 2006;Hoben et al 2007;Mattingly 1991). Expert practice in physiotherapy has been proposed to involve a combination of knowledge, clinical reasoning, movement and virtues (Jensen et al 2000), whilst "master" or expert practice when compared to novice has been shown to be separated by the ability to use time, develop frameworks, communicate, teach, and predict clinical outcomes (Jensen et al 1992).…”
Section: Methods Of Reasoningmentioning
confidence: 99%
“…The musculoskeletal physiotherapy literature surrounding therapists and reasoning suggests that clinicians commonly may generate initial hypotheses and subsequently test them via questioning or physical examination procedures (hypotheticodeductive) in a deductive way from a general presentation resulting to one that is more specific (Jones 1995;Loftus and Smith 2008). They attempt to recognise clinical patterns that have been experienced before (pattern-recognition) (Patel et al 1997), clinicians may create an understanding of the patient story (narrative reasoning) (Mattingly 1991;Mattingly and Fleming 1994) or identify a number of clinical variables that when presented together suggest a treatment plan (clinical prediction) (Childs et al 2004). In addition to these commonly cited musculoskeletal models there are other less familiar methods of reasoning identified such as ethical and procedural: Ethical reasoning requires the knowledge of ethical principles, codes of conduct and professional standards and applies these when confronted by a clinical dilemma (Barnitt & Partridge 1997;Edwards and Delaney 2008).…”
Section: Methods Of Reasoningmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Importantly, clinical reasoning encompasses more than just the process of reaching a diagnosis, which while pivotal, is just part of a range of clinical reasoning strategies at a clinicians' disposal. 17,18,19,20,21 Research in the health sciences has identified the clinical reasoning strategies used in different health professions. While all health professions tend to share common core compo-nents (such as diagnostic, procedural and narrative reasoning), the approach each profession takes to clinical reasoning varies, and a number of different clinical reasoning strategies have been identified though research or proposed theoretically: in nursing; 13,22 in occupational therapy; 17,18,19 and in physiotherapy.…”
Section: Clinical Reasoning In Other Health Professionsmentioning
confidence: 99%
“…17,18,19,20,21 Research in the health sciences has identified the clinical reasoning strategies used in different health professions. While all health professions tend to share common core compo-nents (such as diagnostic, procedural and narrative reasoning), the approach each profession takes to clinical reasoning varies, and a number of different clinical reasoning strategies have been identified though research or proposed theoretically: in nursing; 13,22 in occupational therapy; 17,18,19 and in physiotherapy. 10,20,21,23 Table 1 illustrates the clinical reasoning strategies identified in a range of health professions.…”
Section: Clinical Reasoning In Other Health Professionsmentioning
confidence: 99%